Organizational and pedagogical conditions of scientific and methodological work efficiency in pedagogical higher educational establishments - Repko, I.; Stepanets, I. (Scientific notes of the pedagogical department, 2021)
The article deals with the problem of ensuring scientific and methodological work efficiency in higher educational establishments, in particular pedagogical ones. Based on the analysis and generalization of scientific literature and practical experience, the essence of key concepts is determined: condition; organizational and pedagogical condition, efficiency. Certain aspects of the place and the role of scientific and methodological work in the holistic pedagogical process of higher educational establishment are identified, which provides professional training of students in the context of cooperation pedagogy. The main problems are highlighted and their consideration in the scientific and methodological work planning process is outlined. It is noted that an important condition for the improvement of scientific and methodological work is the concretization of its areas, which are named and meaningfully characterized. Approaches to the development of scientific bases for effective quality management of the educational process in a higher education establishment, a component of which is scientific and methodological work, are proposed. The essence and the significance of the system diagnostics are clarified, the results of which are decisive for the formation of the content and the development of forms of scientific and methodological work in pedagogical higher educational establishment. According to the results of the research, the pedagogical conditions (external and internal) are singled out, the creation of which is conditioned by the efficiency of the formation of scientific and methodical work system in higher educational establishments, their generalized characteristics are presented. The organic interrelation of the professional educational environment, in particular in pedagogical higher educational establishments, with scientific and methodical work, which is its structural element, is illustrated. The influence of high-quality professional educational environment on increasing the level of the methodological competence of both teachers and future ones is stated.